Odpowiedzi

2010-01-17T12:38:56+01:00
2010-01-17T12:40:50+01:00
A)-2-2a+3=
-2a+1

b)2a-3b+3a-2b=
5a-5b

c)2y-6y+4x-2x=
-4y+2x

d)2x+3-6x-10=
-4x- 7

e)-x+2x+(-6)+x-4=
2x-10

f)2a-6-ab-(-3)=
2a-ab- 3

g)3x²-2y²-6x²-2y²=
- 3x²- 4y²

h)3,5b-2,4c-0,6c-0,5b=
3b-3c

i)3x²-2x+1+x-4x²-2=
-x²-x-1

j)2m²+3mn-n+mn+3n-m² =
m²+4mn +2 n
9 4 9
Najlepsza Odpowiedź!
2010-01-17T12:41:05+01:00
A)-2-2a+3= 1- 2a
b)2a-3b+3a-2b = 5a - 5b
c)2y-6y+4x-2x = -4y + 4 - 2x
d)2x+3-6x-10 = -4x - 7
e)-x+2x+(-6)+x-4 = 2x - 10
f)2a-6-ab-(-3) = 2a + 3 - ab
g)3x²-2y²-6x²-2y² = -3x2 - 4y2
h)3,5b-2,4c-0,6c-0,5b = 3 b - 3c
i)3x²-2x+1+x-4x²-2 = -x2 - x -1
j)2m²+3mn-n+mn+3n-m² = m2 + 4mn + 2n

Pozdrawiam :)
49 4 49